Quantitative assessment of maternal biomarkers related to one-carbon metabolism and neural tube defects - Tang, Ke-Fu (Sci Rep, 2015)
Periconceptional supplementation with folic acid reduces the occurrence of neural tube defects (NTDs). The association between maternal abnormalities in homocysteine metabolism (e.g., hyperhomocysteinaemia, folate deficiency and low vitamin B12) and the risk of NTDs-affected pregnancies has been widely evaluated in recent years, although the results are conflicting. To investigate this inconsistency, we performed a meta-analysis of 32 studies, involving 1,890 NTD-affected mothers and 3,995 control mothers, to develop an understanding of the relationship between maternal biomarkers related to one-carbon metabolism and NTD. A random-effects model was used to calculate the ratio of means (RoM) between the cases and controls, along with the 95% confidence intervals (CIs). A significant increase in homocysteine levels was observed in NTD-affected mothers compared with controls (RoM: 1.16, 95% CI: 1.09–1.23, P = 1.8 × 10(−6)). The pooled analysis also revealed that NTD-affected mothers had significantly lower levels of folate (RoM: 0.93, 95% CI: 0.88–0.97, P = 0.002), vitamin B12 (RoM: 0.91, 95% CI: 0.87–0.95, P = 3.6 × 10(−5)) and red blood cell folate (RoM: 0.92, 95% CI: 0.86–0.98, P = 0.01). Therefore, altered plasma levels of biomarkers related to one-carbon metabolism are associated with NTD-affected pregnancies.